Adaptive decision feedback equalization for filter bank based multicarrier systems - Waldhauser, D.S.; Baltar, L.G.; Nossek, J.A. (2009 IEEE International Symposium on Circuits and Systems (ISCAS), 2009)
In this work we present a per-subchannel nonlinear adaptive equalizer for a class of filter bank based multicarrier (FBMC) systems. We consider the class of exponentially modulated FBMCs with offset quadrature amplitude modulated (OQAM) input symbols. We present a fractionally spaced adaptive decision feedback equalizer (DFE) based on the least-mean-square (LMS) algorithm. The input of each equalizer comprises only the output of each subchannel. In the simulation results we show that, despite its increased computational complexity, the performance and higher bandwidth efficiency of OQAM FBMC systems makes them a competitive alternative to conventional multicarrier systems like cyclic prefix based orthogonal frequency division multiplexing (CP-OFDM).